Could endocrine stimuli regulate fibroblasts/myofibroblasts dynamics during skin wound healing? A systematic review of preclinical models - Souza, André de (2022)
Fibroblasts and myofibroblasts are important cells involved in wound contraction, as well as in the synthesis of important components of the extracellular matrix (ECM). However, the main mechanisms involved in the differentiation of myofibroblasts after exposure to hormones are poorly understood. Therefore, the aim of this study was to systematically review the action of endocrine stimulation on myofibroblasts during the cutaneous wound healing process using in vitro and in vivo analyses. In addition, we performed a critical review of the methodological quality of these studies using the SYRCLES risk of bias. The databases searched were PubMed/Medline, Scopus and Web of Science, and only original studies were analyzed according to the PRISMA guidelines. In vivo studies have shown that lipid hormones such as testosterone, estrogen and 17-b estradiol stimulate myofibroblast differentiation while DHT impairs this process by increasing the level of pro-inflammatory cytokines and blocking the expression of TGF-β through the signaling pathway. of the Androgen Receptor (AR)- Smad3. The peptide hormone GH, in addition to promoting the increase of the IGF-1, extension of the inflammatory phase, inhibits the differentiation of fibroblasts into myofibroblasts induced by TGF-β, while the glucagon-like peptide (GLP-1) and the hormone GHRH and dexamethasone (DX) reduce the expression of inflammatory markers such as COX-2 and increase the expression of α-SMA, promoting wound contraction. In in vitro analyses, the peptide hormone GHRH promoted an increase in α-SMA labeling, while GH reduced these markers, corroborating the in vivo analyses. The main pathways studied were TGF-β/Smad, MAPk and blockade of pro- inflammatory pathways such as NFKb. Furthermore, it was observed that the dose varies from 1 to 10mg/k of estrogen and 17-β estradiol as well as 2mg of dexamethasone increase staining for myofibroblasts and in GLP-1 and GHRH, doses of 3mg/k and 100nM respectively. The studies present heterogeneous data and have methodological limitations, however, the similarity between some studies allowed the performance of a meta-analysis considering an experimental model, treatment time and doses, leading to consistent results and greater reliability. This study is registered on the PROSPERO platform (CRD42021264735). Keywords: Endocrine regulation. Hormones. Myofibroblasts. Healing.